Evaluation of nitrogen-delivery methods for stocker cattle grazing annual ryegrass. Issue 2 (19th March 2021) - Gunter, Phillip A; Mullenix, Mary K; Burdette, Lance C; Muntifering, Russell B
Abstract: A 2-yr grazing experiment was conducted to evaluate efficacy of nitrogen (N) fertilization, interseeded legumes, and protein supplementation for N delivery to stocker cattle grazing annual ryegrass ( Lolium multiflorum ). Each year, 90 steers (initial BW, 241 ± 13 kg) were assigned to the following N-delivery methods, with or without monensin fed in a free-choice mineral supplement as a 5 × 2 factorial arrangement of treatments: ryegrass fertilized with 112 kg N/ha (NFERT); ryegrass interseeded with crimson clover (CC, Trifolium incarnatum ); ryegrass interseeded with arrowleaf clover (AC, Trifolium vesiculosum ); ryegrass plus distillers dried grains with solubles (DDGS) supplemented at 0.65% BW daily; and ryegrass plus whole cottonseed (WCS) supplemented at 0.65% BW daily. Pastures within the interseeded-clover and protein-supplementation treatments were fertilized with 56 kg N/ha at time of establishment. Steers were weighed every 28 d, and forage mass (FM, kg DM/ha) was measured concurrently using the destructive harvest/disk meter double-sampling method. Each of 30 0.81-ha paddocks was stocked initially with 3 "tester" steers, and stocking density (steers/ha) was adjusted using "put-and-take steers" based on changes in FM and steer BW in order to maintain a uniform forage allowance (FA) of 1 kg DM/kg steer BW. Grazing was discontinued on May 11, 2016 in Yr 1 and May 10, 2017 in Yr 2 following 140 and 84 d of grazing, respectively. Data were analyzed as a completely randomized design with repeated measures for which pasture ( n = 3) was the experimental unit. Ionophore inclusion did not affect ( P > 0.10) any variable measured. Mean FM differed ( P < 0.0001) between years and among N-delivery methods ( P < 0.10), and mean FA differed ( P = 0.005) among N-delivery methods. Steer ADG differed among N-delivery methods ( P = 0.02) and between years ( P < 0.001), whereas total gain/ha differed ( P < 0.0008) among N-delivery methods, but not between years ( P = 0.78). Stocking density differed among N-delivery methods ( P = 0.02) and between years ( P < 0.0001), and grazing-days/ha differed between years ( P < 0.0001) and among N-delivery methods ( P = 0.001). Results indicate that supplementation with a high-protein by-product feed for cattle grazing annual ryegrass maintained ADG, total gain/ha and grazing-days/ha compared with N-fertilized annual ryegrass, and increased ADG, total gain/ha, and grazing-days over interseeded legumes.